Respuestas
Respuesta dada por:
6
x+2y=a
x=a-2y ............(1)
x-2y=b
x=b+2y............(2)
(1)=(2)
a-2y=b+2y
(a-b)=2y+2y
(a-b)/4= y ...(3)
de (1)
x=a-2y
x=a-[ 2(a-b)/4]
x=a-(a/2)+(b/2)=(a/2)+(b/2)=(1/2)(a+b)
x=(1/2)(a+b) ...........(4)
nos piden xy de (3)y(4)
xy=(a+b)/2 * (a-b) /4=(a+b)(a-b)/8=(a²-b²)/8
rpta :
xy=(a²-b²)/8
x=a-2y ............(1)
x-2y=b
x=b+2y............(2)
(1)=(2)
a-2y=b+2y
(a-b)=2y+2y
(a-b)/4= y ...(3)
de (1)
x=a-2y
x=a-[ 2(a-b)/4]
x=a-(a/2)+(b/2)=(a/2)+(b/2)=(1/2)(a+b)
x=(1/2)(a+b) ...........(4)
nos piden xy de (3)y(4)
xy=(a+b)/2 * (a-b) /4=(a+b)(a-b)/8=(a²-b²)/8
rpta :
xy=(a²-b²)/8
Respuesta dada por:
1
Respuesta:
nose ni siquira
Explicación paso a paso:
Preguntas similares
hace 6 años
hace 6 años
hace 9 años